Forebrain E-I balance controlled in cognition through coordinated inhibition and inhibitory transcriptome mechanism - Tian, Tian; Cai, You; Qin, Xin; Wang, Jiangang; Wang, Yali; Yang, Xin (Frontiers in Cellular Neuroscience, 2023)
Forebrain neural networks are vital for cognitive functioning, and their excitatory-inhibitory (E-I) balance is governed by neural homeostasis. However, the homeostatic control strategies and transcriptomic mechanisms that maintain forebrain E-I balance and optimal cognition remain unclear. In this study, we investigated the patterns of neural network homeostasis by suppressing forebrain excitatory neural activity and spatial training. We found that inhibitory transmission and receptor transcription were reduced in tamoxifen-inducible Kir2.1 conditional knock-in mice. In contrast, spatial training increased inhibitory synaptic connections and the transcription of inhibitory receptors. Our study provides significant evidence that inhibitory systems play a critical role in the homeostatic control of the E-I balance in the forebrain during recognition training and E-I rebalance, and we have provided insights into multiple gene candidates for cognition-related homeostasis in the forebrain.